IMPORTANCE OF LISTENING IN LANGUAGE LEARNING AND LISTENING COMPREHENSION PROBLEMS: THE EXPERIENCE OF LANGUAGE LEARNERS (Scientific journal of the Fergana State University, 2023)
The ability to listen plays an important role in effective communication with people both in everyday life and in the educational context. Despite the importance of listening for the development of communication and cognitive skills, for many years it was not given due attention in language training programs. Although there are many different points of view on how to learn to listen, the success of each point of view depends on solving and minimizing the critical problems faced by language learners. This article aims to explore concepts and issues related to the role and importance of listening comprehension skills in learning German as a foreign language.